Pelatihan dan Lomba Membuat Jajanan Sehat Yang Memenuhi Kebutuhan Gizi Anak Sekolah - Gardiarini, Praseptia; Dianovita, Chardina; Farida, Farida; Retno, Nawang (Universitas Nusantara PGRI Kediri, 2020)
School age children need a balance nutritions to support their growth and development. The optimal growth and development can be reach only if the balances of nutritions consume well. Adequacy of good nutrition doesn’t only come from the main food but also supported by snacks consumed by shool children, for that the production of healthy snacksalso needs attention. Rumah Kumbang is child care community focuses on character building activities and the development of children’s potential. The aim of this community service aim is to train the member of Rumah Kumbang to be able to produce healthy snacks that consist balance nutrition for school age children. The methode in this community service is to provide material exposure, product manufacturing training and a healthy food creation competition. The result is the participants of this community service gain knowledge and motivation to produce healthy and nutritious snacks. In conclusion, after doing this community service, further assistance is needed in relation to healthy snack production process in Rumah Kumbang Community so it can be marketed in wider community